Expresión ¬(A∨B∧C)
El profesor se sorprenderá mucho al ver tu solución correcta😉
Solución
Solución detallada
¬(a∨(b∧c))=¬a∧(¬b∨¬c)
¬a∧(¬b∨¬c)
Tabla de verdad
+---+---+---+--------+
| a | b | c | result |
+===+===+===+========+
| 0 | 0 | 0 | 1 |
+---+---+---+--------+
| 0 | 0 | 1 | 1 |
+---+---+---+--------+
| 0 | 1 | 0 | 1 |
+---+---+---+--------+
| 0 | 1 | 1 | 0 |
+---+---+---+--------+
| 1 | 0 | 0 | 0 |
+---+---+---+--------+
| 1 | 0 | 1 | 0 |
+---+---+---+--------+
| 1 | 1 | 0 | 0 |
+---+---+---+--------+
| 1 | 1 | 1 | 0 |
+---+---+---+--------+
¬a∧(¬b∨¬c)
Ya está reducido a FNC
¬a∧(¬b∨¬c)
(¬a∧¬b)∨(¬a∧¬c)
(¬a∧¬b)∨(¬a∧¬c)